2018
DOI: 10.1038/s41467-018-04386-3
|View full text |Cite
|
Sign up to set email alerts
|

Probing the pathways of free charge generation in organic bulk heterojunction solar cells

Abstract: The fact that organic solar cells perform efficiently despite the low dielectric constant of most photoactive blends initiated a long-standing debate regarding the dominant pathways of free charge formation. Here, we address this issue through the accurate measurement of the activation energy for free charge photogeneration over a wide range of photon energy, using the method of time-delayed collection field. For our prototypical low bandgap polymer:fullerene blends, we find that neither the temperature nor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
149
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 66 publications
15
149
0
Order By: Relevance
“…First, free charge generation does not benefit from a larger driving force (channel I vs channel II) nor from excess photon energy. These findings substantiate the conclusions from earlier studies on fullerene‐based solar cells, which were interpreted in terms of a cold generation process, involving a low energy CT state manifold as a precursor to free charges . Second, the lack of a field dependence of generation, independent of the excitation energy, suggests a low energetic barrier for the dissociation of such low energy precursor states.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…First, free charge generation does not benefit from a larger driving force (channel I vs channel II) nor from excess photon energy. These findings substantiate the conclusions from earlier studies on fullerene‐based solar cells, which were interpreted in terms of a cold generation process, involving a low energy CT state manifold as a precursor to free charges . Second, the lack of a field dependence of generation, independent of the excitation energy, suggests a low energetic barrier for the dissociation of such low energy precursor states.…”
supporting
confidence: 88%
“…Notably, the activation energy for CT dissociation is unaffected by entropic effects . Temperature‐dependent studies on fullerene‐based blends revealed activation energies for CT dissociation from few tens to ≈100 meV, with some important exemptions as discussed next. We are aware of only one publication reporting temperature‐dependent measurements on the CT binding in a NFA blend .…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Merging the properties of three‐dimensional buckyballs (or buckybowls) and covalent‐organic frameworks (COFs) provides access to a novel class of materials combining ultrafast energy/electron transport characteristic of three‐dimensional (3D) fulleretic linkers with high modularity, crystallinity, and surface area, which are intrinsic properties of COFs . The precise donor–acceptor alignment achieved in the materials is imposed by the rigid COF scaffold and is crucial for efficient energy or charge transfer as it can influence the distance of exciton diffusion, π–π stacking, or Förster radius, and as a result, can enhance device performance …”
Section: Introductionmentioning
confidence: 99%
“…These processes highly depend on optoelectronic properties of a given donor (D), acceptor (A), and D:A interface. At the interface, build‐in intermolecular charge transfer (CT) states that act as intermediate states between the photo‐generated Frenkel exciton (FE) and charge separation (CS) states play a dominant role in the electron–hole dissociation . Nevertheless, little is known from spin‐dependent dissociation and recombination channels in the NFA system …”
Section: Introductionmentioning
confidence: 99%